Putting Reusability First: A Paradigm Switch in Remote Laboratories Engineering - Gravier, Christophe; Fayolle, Jacques; Lardon, Jérémy; Bayard, Bernard; Dusser, Gaétan; Vérot, Romain (International Journal of Online and Biomedical Engineering (iJOE), 2009)
In this paper, we present a new devices brought online thanks to our Collaborative Remote Laboratories framework. Whereas previous devices integrated in our remote laboratory belongs to the domain of electronics, such as Vector Network Analyzers, the devices at the concern in this paper are, on one hand, an antenna workbench, and on the other, an homemade switching device, which embeds several electronic components. Because the middleware and framework for our environment were designed to be reusable, we wanted to put it to the test by integrating new and different devices in our Online Engineering catalog. After presenting the devices to be put online, we will expose the software development efforts required in regards to the reusability of the solution. As a consequence, the expose work and results tend to make the Online Engineering software architects to think reusability first, breaking with the current trends to implement Remote Labs one after the other, without much reusability, apart the capitalized experience. In this, we defend a paradigm switch in our current engineering approaches for Remote Laboratories implementations: Reusability should be thought first.